Позаурочна форма навчання та сучасні компоненти її реалізації у ЗЗСО - Лаврентьєв, Олександр Миколайович; Сергієнко, Юрій Петрович; Деркач, Оксана Вікторівна (Український державний університет імені Михайла Драгоманова, 2026)
У статті аналізуються питання раціональної побудови позаурочних навчальних занять для школярів. Організація таких занять спрямована на гармонійний розвиток фізичних якостей учнів і підвищення рівня їхньої рухової активності, що нині є однією з актуальних проблем у сфері організації активного дозвілля молоді. Основними засобами реалізації виступають фізичні вправи, а методи організації навчально-виховного процесу визначаються характером взаємодії між учителем і учнем. Сучасні умови зумовлюють необхідність переосмислення підходів до організації занять з фізичної культури. Так раціонально вибудувана позаурочна діяльність може розглядатися як ефективний спосіб надання учням додаткової освіти з обраного виду спорту та як важливий чинник зростання їхньої рухової активності. Досягнення високих результатів можливе лише за умови системного підходу та використання різноманітних форм роботи. Створення в школі гуртків і спортивних секцій для різновікових груп, а також проведення внутрішньо-шкільних змагань з різних видів спорту відкриває можливості для вдосконалення спортивних навичок, організації змістовного дозвілля відповідно до інтересів учнів і сприяє розширенню їхнього кола спілкування.

The article analyzes the issues of rational construction of extracurricular educational classes for schoolchildren. The organization of such classes is aimed at the harmonious development of students' physical qualities and increasing the level of their motor activity, which is currently one of the urgent problems in the field of organizing active leisure of young people. The main means of implementation are physical exercises, and the methods of organizing the educational process are determined by the nature of the interaction between the teacher and the student.Modern conditions necessitate a rethinking of approaches to organizing physical education classes. Thus, according to the results of various studies, it has been established that only about 9% of adolescents have alevel of physical development and health approaching the norm, while approximately 38% of adolescents have chronic diseases. The prevalence of diseases associated with the cardiovascular and musculoskeletal systems is growing especially rapidly, which indicates a low level of motor activity. The causes of these diseases are complex and are caused not so much by medical, but by social and pedagogical factors. Based on the above, we can state that the organization of extracurricular physical education and sports activities will help to accustom people to physical exercises at all stages of life.)Extracurricular activities, rationally structured in this way, can be considered as an effective way of providing students with additional education in the chosen sport and as an important factor in increasing their physical activity. Achieving high results is possible only with a systematic approach and the use of various forms of work. The creation of clubs and sports sections for different age groups at school, as well as holding intra-school competitions in various sports, opens up opportunities for improving sports skills, organizing meaningful leisure activities in accordance with the interestsof students, and helps to expand their circle of communication.
Extra-curricular form of learning and modern components of its implementation
Keywords: викладач; учень; фізичні вправи; позаурочна форма навчання; дозвілля; шкільні змагання; гра; естафета; спілкування; teacher; student; physical exercises; extracurricular form of learning; leisure; school competitions; game; relay race; communication